Pemanfaatan Limbah Kotoran Ternak Menjadi Biogas dan Pupuk Organik untuk Meningkatkan Kesejahteraan Masyarakat Desa Laikang - Sahrul Alam; Asrul; Miftahul Khaer; Nur Ilmi Azzahrah; Moh. Ahsan S. Mandra; A. M. Taufik Ali (Joong-Ki : Jurnal Pengabdian Masyarakat, 2022)
Livestock waste, in Desa Laikang, Kecamatan Mangarabombang, Kabupaten Takalar has not been widely used by the community, so that it often only pollutes the environment. Even though if it is processed properly, it will produce economic added value and prevent environmental pollution. This is due to the lack of socialization and training about biogas technology, the lack of community knowledge and skills regarding the application of biogas digester installation technology. This program aims to empower the Desa Laikang community through processing livestock waste into alternative fuels (biogas) and organic fertilizer from biogas processing waste (bio slurry) to support energy independence, renewable energy and food security programs. The method used in this activity was Participatory Action and Learning (PLA). The results achieved from this activity are: (1) construction of 1 (one) unit of biogas digester installation with a capacity of 4 m3, (2) organic fertilizer from bio slurry, (3) clean and hygienic cattle pens also environmental friendly, (4) demonstration plot of agriculture application of organic fertilizer, and (5) the formation of a new community (group) in Desa Laikang.